Herons in Aquafarms Are More Fearful of Humans - Shuang Yang; Sidan Lin; Wei Liang (Ecology and Evolution, 2025)
ABSTRACT Herons (Ardeidae), an important group in wetland ecosystems, have a particularly strong relationship with humans. However, their predation on farmed fish and shrimp in aquafarms can lead to economic losses for local fish farmers. Consequently, notable conflicts arise between fish farmers and herons. Fish farmers adopt various measures to deter herons from “stealing” their fish; however, there is limited research on the behavioral responses of herons under such pressures of human disturbance. Flight initiation distance (FID) is an important manifestation of avian anti‐predation behavior and serves as an indicator of birds' tolerance to human disturbance. This study investigated the potential variations in tolerance to human disturbance between the little egret (Egretta garzetta) and the Chinese pond heron (Ardeola bacchus) in “stealing” environments (aquafarm environments) and non‐aquafarm environments in Hainan and Guangdong Provinces, south China, using FID as an indicator. Herons in aquafarm environments were less tolerant (having longer FIDs) to human disturbance compared to herons in non‐aquafarm environments. The main cause of this phenomenon could be the harsh deterrents used by humans to prevent herons from “stealing” fish. These deterrents increase the predation risk for herons when “stealing” in aquafarms, causing them to exhibit less tolerance to human disturbance. Our study increases understanding of the behavioral response patterns of herons in human–wildlife conflicts and provides valuable insights for more scientific and rational management and protection of Ardeidae species.